A new scanning mode to improve scanning ion conductance microscopy imaging rate with pipette predicted movement. (October 2017) - Zhuang, Jian; Jiao, Yangbohan; Mugabo, Vincent
Highlights: A new scanning mode with pipette predicted movement is proposed for scanning ion conductance microscope (SICM). The pipette scanning trajectory is optimized and the imaging rate is improved in the new scanning mode. The approach curve of the pipette horizontally moving to the cliff structure is researched by finite element analysis. The topography of PDMS surface, mice cardiac fibroblasts and breast cancer cells are measured in the new scanning mode. Abstract: Scanning ion conductance microscopy (SICM) is a non-contact surface topography measurement technique that has been increasingly used for soft surfaces such as living biological samples. An approach-retract scanning (ARS) mode is widely used to avoid collision between the SICM probe ( i.e., pipette) and an abrupt increase in sample profile. However, the redundant pipette trajectory in the ARS mode lengthens the scan time, thus reducing SICM efficiency and time resolution. To avoid this problem, a new scanning mode is discussed that adds horizontal movement at each measurement point to predict the upcoming sample topography via variation in ion current. The pipette then retracts in response to raised topography, while it raster scans flat or downhill topography. The feasibility was verified by finite element analysis and experimental tests on three kinds of soft samples: polydimethylsiloxane, mice cardiac fibroblasts, and breast cancer cells. The pixel detection frequency during imaging and the mean square error of the sample topography were compared for the two modes. The new scanning mode enhances the SICM imaging rate without loss of imaging quality or scanning stability, while it increases efficiency and time resolution. It thus has an improved performance for characterizing biological samples.